2004
DOI: 10.1128/jvi.78.5.2242-2246.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Hypersusceptibility to Protease Inhibitors and Low Replicative Capacity of Human Immunodeficiency Virus Type 1 Strains in Primary Infection

Abstract: The initial virus strains from as many as 12% of individuals with primary human immunodeficiency virus (HIV) infection have a 50% inhibitory concentration <0.4-fold that of HIV type 1 NL4-3 (HIV-1 NL4-3 ) to ritonavir (hypersusceptibility [HS]). There is also substantial variation in replicative capacity (RC) or an in vitro assay of the contributions of protease (PR) and reverse transcriptase to viral fitness. In chronically infected antiretrovirally treated patients, amprenavir HS has been associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For example, drug resistance by a wild type PR is increased by substitutions that map exclusively in the p7 NC /p1 cleavage site (Nijhuis et al, 2007), while wild type PR among viruses from therapy naïve individuals display hypersusceptibility to PI (Leigh Brown et al, 2004; Martinez-Picado et al, 2005) The Gag mutations identified in our study accumulated concomitantly with PR mutations in the presence of PI and persisted over time, similar to characteristics of amino acid residues in PR that confer drug resistance. Indeed, the predominant effect for most of the drug-associated amino acid substitutions in Gag-Pol in our study was to enhance resistance to inhibitors, as any reversions to pretherapy residues increased drug sensitivity.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…For example, drug resistance by a wild type PR is increased by substitutions that map exclusively in the p7 NC /p1 cleavage site (Nijhuis et al, 2007), while wild type PR among viruses from therapy naïve individuals display hypersusceptibility to PI (Leigh Brown et al, 2004; Martinez-Picado et al, 2005) The Gag mutations identified in our study accumulated concomitantly with PR mutations in the presence of PI and persisted over time, similar to characteristics of amino acid residues in PR that confer drug resistance. Indeed, the predominant effect for most of the drug-associated amino acid substitutions in Gag-Pol in our study was to enhance resistance to inhibitors, as any reversions to pretherapy residues increased drug sensitivity.…”
Section: Discussionmentioning
confidence: 56%
“…Resistance to PI can be attributed to multiple mechanisms. For example, polymorphisms in PR known to reduce or increase sensitivity to PI can occur in therapy-naïve patients (Brown et al, 1999; Lech et al, 1996; Leigh Brown et al, 2004; Martinez-Picado et al, 2005; Perez et al, 2001; Rose et al, 1996). In addition, as a result of suboptimal drug therapy, viruses begin to accumulate mutations in PR in a stepwise fashion (Condra et al, 1996; Erickson et al, 1999; Molla et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is attractive to speculate that the extended antiviral activities of protease inhibitors are, in part, derived from the restoration of the antiviral activity of m 6 A reader proteins such as YTHDF3. Viral hypersusceptibility to protease inhibitors as well as mutations in Gag that modulate the amount of mature protease produced have been described [32,33]. Future studies are needed to determine the true antiviral potency and breadth of the YTHDF3 protein when combined with protease inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…We then obtained the means for the measures that we used for evaluation of classifiers. Cross validation gives realistic evaluation of model performance as done in some studies [ 58 , 59 ]. Parameter tuning of model parameters and cross validation was done with help of ‘caret’ R package [ 60 ].…”
Section: Methodsmentioning
confidence: 99%